Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma. (29th March 2012) - Krisanaprakornkit, Suttichai; Iamaroon, Anak
Abstract : Oral cancer is one of the drastic human cancers due to its aggressiveness and high mortality rate. Of all oral cancers, squamous cell carcinoma is the most common accounting for more than 90%. Epithelial-mesenchymal transition (EMT) is suggested to play an important role during cancer invasion and metastasis. Recently, emerging knowledge on EMT in carcinogenesis is explosive, tempting us to analyze previous studies on EMT in oral squamous cell carcinoma (OSCC). In this paper, we have first addressed the general molecular mechanisms of EMT, evidenced by alterations of cell morphology during EMT, the presence of cadherin switching, turning on and turning off of many specific genes, the activation of various signaling pathways, and so on. The remaining part of this paper will focus on recent findings of the investigations of EMT on OSCC. These include the evidence of EMT taking place in OSCC and the signaling pathways employed by OSCC cells during their invasion and metastasis. Collectively, with the large body of new knowledge on EMT in OSCC elaborated here, we are hopeful that targeting treatment for OSCC will be developed.